Electronic field data collection system for highway inspection maintenance - Mohd. Ghazalee, Nor Husna (2012)
Compared to traditional maintenance inspection with paper sheets, electronic maintenance data collection can improve maintenance data management. The traditional process of collecting highway inspection data is based on paper sheets where the records are to be filed manually. The inspection in paper based is hard to be used whereby the inspector need to take out pen from his pocket to write up the inspection data manually, measure the length in critical condition such as slope and also need to bring camera to take the photos. Therefore, an Electronic Field Data Collection System (EFDCS) has been approached in this research for helping the inspectors to collect and record the field inspection data. The system uses a Tablet PC as a device to collect and record the inspection data. The objectives of this study are to review the current practice of field inspection process in highway maintenance; to develop a prototype of Electronic Field Data Collection System (EFDCS) for highway inspection maintenance by using the technology of Tablet PC and to address the potential and limitation of Electronic Field Data Collection System (EFDCS) in highway inspection maintenance. Data were collected from Malaysian Highway Authority (MHA) and Senai Desaru Expressway Berhad (SDE) by means of interviews and structured interview questionnaires. The prototype of Electronic Field Data Collection System (EFDCS) was developed by using two type of Android application software; D atadroid and Smart Measure. The finding showed that the Electronic Field Data Collection System (EFDCS) has a great potential in field inspection maintenance as the system able to increase the accuracy of collecting field data, reduce the tools and equipment of inspection, prevent duplication of data, eliminate re-entry of data and speed up the inspection time.